Rapid Emergence of Daptomycin Resistance in Nonstriatum Corynebacterium Species: A Multicenter Study. (11th September 2019) - Mitchell, Kaitlin; McElvania, Erin; Wallace, Meghan; Robertson, Amy; Westblade, Lars; Burnham, Carey-Ann
Abstract: Members of the genus Corynebacterium are increasingly recognized as causes of opportunistic infection; some species can be multidrug resistant, posing a treatment challenge. Daptomycin is frequently used as therapy of last resort in this setting, but previous work from our group demonstrated the ability of C striatum clinical isolates to rapidly develop high-level resistance to daptomycin, both in vivo and in vitro. Here, our objective was to expand this investigation into a multicenter study evaluating multiple Corynebacterium species. Corynebacterium strains from three tertiary-care academic medical centers (total, n = 76; site 1, n = 44; site 2, n = 15; site 3, n = 17) were evaluated, representing 16 species. Isolates were identified during routine clinical testing and reported to species level in accordance with each laboratory's standard operating procedures. Identification of each species was confirmed using both VITEK MS and Bruker BioTyper MALDI-TOF MS. MICs to daptomycin (Etest), vancomycin (Etest), and telavancin (Liofilchem) at baseline were determined using gradient diffusion methods on Mueller-Hinton agar with blood (Hardy Diagnostics). Each isolate was then inoculated in duplicate to 5 mL Tryptic Soy Broth. A daptomycin Etest was submerged in one tube from each pair, and growth was observed after 24-hour incubation. If turbidity was observed in the tube with daptomycin, MICs for each of the 3 antimicrobials were reassessed. High-level daptomycin resistance emerged in 24 strains: C aurimucosum (1/1 isolate tested), C bovis (1/2), C jeikeium (2/11), C macginleyi (3/3), C resistens (1/1), C simulans (1/1), C striatum (14/14 isolates), and C ulcerans (1/1). The majority of these isolates had MIC values >256 µg/mL following exposure to daptomycin. Forty-eight other isolates remained susceptible to daptomycin: C afermentans (1/1), C amycolatum (19/20), C diphtheriae (1/1), C jeikeium (7/11), C kroppenstedtii (2/2), C propinquum (3/3), C pseudodiphtheriticum (6/6), C tuberculostearicum (0/6), and C urealyticum (0/3). Many of these isolates did not undergo MIC testing postdaptomycin exposure in broth due to complete lack of growth. Among those that did (n = 19), the median daptomycin MIC was 0.38 µg/mL (mean 0.42 µg/mL; range 0.023-1.0 µg/mL). One isolate of C bovis and two isolates of C jeikeium yielded variable susceptibility to daptomycin; a subset of resistant colonies grew adjacent to the gradient diffusion strip. Upon isolation and further MIC testing, these colonies maintained high-level resistance. In addition, one isolate of C amycolatum exhibited high-level daptomycin resistance (MIC >256 µg/mL) prior to in vitro exposure. All isolates in the cohort were susceptible to vancomycin and telavancin, both before and after daptomycin exposure. Our findings suggest that multiple Corynebacterium species can rapidly develop high-level daptomycin resistance after a short period of exposure to this antimicrobial. This finding has important clinical implications, especially in the treatment of invasive infections or infections of indwelling medical devices.